The role of proline rich tyrosine kinase 2 (Pyk2) on cisplatin resistance in hepatocellular carcinoma. - Wei Geng; Kevin T P Ng; Chris K W Sun; Wing Lung Yau; Xiao Bing Liu; Qiao Cheng; Ronnie T P Poon; Chung Mau Lo; Kwan Man; Sheung Tat Fan (PLoS ONE, 2011)
AIMS: We previously demonstrated Proline rich tyrosine kinase 2 (Pyk2) plays important roles in regulating tumor progression, migration and invasion in hepatocellular carcinoma (HCC). In this study, we aimed to examine the role of proline rich tyrosine kinase 2 (Pyk2) on cisplatin resistance in HCC and to explore its underlying molecular mechanism. METHODOLOGY/PRINCIPAL FINDINGS: Stable transfectants either overexpressing or suppressing Pyk2 were established in different HCC cell lines. MTT, colony formation and Annexin-V assays were employed to examine their in vitro responses to cisplatin. Xenograft ectopic and orthotopic nude mice models were generated to investigate the in vivo responses of them to cisplatin treatment. cDNA microarray was performed to identify Pyk2-induced genes which were further validated by quantitative real-time RT-PCR using clinical HCC samples. In vitro functional study demonstrated that Pyk2-overexpressing HCC transfectants exhibited relatively lower cytotoxicity, higher colony-forming ability and lower apoptosis to cisplatin compared with the control transfectants. Moreover, Pyk2 overexpressing HCC transfectants had a higher survival rate under cisplatin treatment by up-regulation of AKT phosphorylation. In vivo xenograft nude mice model demonstrated that Pyk2-overexpressing transfectants developed higher tolerance to cisplatin treatment together with less tumor necrosis and apoptosis. cDNA microarray analysis revealed that there were more than 4,000 genes differentially expressed upon overexpression of Pyk2. Several upregulated genes were found to be involved in drug resistance and invasion in cancers. Among them, the expression profiles of MDR1, GAGE1, STAT1 and MAP7 were significantly associated with the expression of Pyk2 in clinical HCC samples. CONCLUSIONS: Our results may suggest a new evidence of Pyk2 on promoting cisplatin resistance of HCC cells through preventing cell apoptosis, activation of AKT pathway and upregulation of drug resistant genes.